International Management: Text and Cases - W. Beamish Paul (Mc Graw Hill Irwin, 2003)
Beamish, Morrison, Rosenweig and Inkpen’s, International Management, 5e is an “international”, international-management book. It looks at how firms become and remain international in scope. The first four editions were used in hundreds of universities and colleges in over 20 countries. The book focuses on issues of international management common and important to business people “everywhere”. It is about the experiences of firms of all sizes, from many countries and regions (North America, South America, Western Europe, Eastern Europe, Middle East, Asia, Africa, etc.), as they come to grips with an increasingly competitive global environment. It is about the practice of management when a home-market perspective is no longer enough to achieve and sustain success. Through carefully selected comprehensive case studies and integrated text material, this book bridges both the internationalization process and multinational management. Beamish, Morrison, Rosenzweig and Inkpen , four highly-experienced international business teachers/researchers, offer an integrated text and casebook which has been constantly refined and updated for over a decade.